2022
DOI: 10.1002/uog.24929
|View full text |Cite
|
Sign up to set email alerts
|

Midgestation cardiovascular phenotype in women who develop gestational diabetes and hypertensive disorders of pregnancy: comparative study

Abstract: Objective Women with gestational diabetes mellitus (GDM) and/or hypertensive disorders of pregnancy (HDP) are at increased long‐term cardiovascular risk. Mild cardiac functional alterations have been detected in women with GDM or HDP in midgestation, prior to clinical onset of the disease, but these functional alterations have not been found to be useful as screening tools. In contrast, increased impedance to peripheral blood flow, measured by echocardiography or ophthalmic artery Doppler, has been shown to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this study, we have demonstrated for the first time an increase in ophthalmic artery PSV ratio in women with GDM. In our previous second-trimester study, before diagnosis of GDM, there was no increase in the ophthalmic artery PSV ratio 17 . These findings suggest progressive or more advanced vascular disease with development of GDM.…”
Section: Comparison With Findings Of Previous Studiesmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, we have demonstrated for the first time an increase in ophthalmic artery PSV ratio in women with GDM. In our previous second-trimester study, before diagnosis of GDM, there was no increase in the ophthalmic artery PSV ratio 17 . These findings suggest progressive or more advanced vascular disease with development of GDM.…”
Section: Comparison With Findings Of Previous Studiesmentioning
confidence: 64%
“…In a first‐trimester screening study, we found that, in 105 women who subsequently developed GDM, compared with 6736 who did not develop GDM, there were increased carotid–femoral pulse‐wave velocity and central systolic blood pressure 4 . In a second‐trimester screening study involving 5214 women, we found that, in 509 women who subsequently developed GDM, maternal hemodynamics, including cardiac output, peripheral vascular resistance and ophthalmic artery PSV ratio, were not significantly different from those in the non‐GDM group 17 . In a cross‐sectional third‐trimester study, we used a handheld pressure tonometer in the radial artery and found that, in 34 women with GDM, compared with 34 non‐diabetic controls, aortic stiffness and augmentation index were marginally increased 3 .…”
Section: Discussionmentioning
confidence: 79%